THE ROLE OF THE KOLAKA REGENCY ELECTION SUPERVISORY AGENCY IN PREVENTING MONEY POLITICS IN THE 2024 ELECTION: PERAN BADAN PENGAWAS PEMILU KABUPATEN KOLAKA DALAM PENCEGAHAN MONEY POLITIC PADA PEMILU 2024 - Dedihasriadi, La Ode; Ananda, Adhe Ismail (Constitutional Law Society, 2025)
This study aims to analyze the effectiveness of the role of the Kolaka Regency Election Supervisory Agency (Bawaslu) in preventing the practice of money politics in the 2024 election and identify its inhibiting factors. This study uses a juridical-empirical method with a descriptive qualitative approach. Primary data was obtained through direct interviews with members of the Kolaka Regency Bawaslu, while secondary data came from official documents, laws and regulations, and related literature. The results of the study show that although Bawaslu has carried out its supervisory duties, challenges such as limited human resources, low legal awareness of the community, and obstacles in proving the practice of money politics are significant obstacles in prevention. This study provides recommendations to increase the capacity of Bawaslu and strengthen the role of the community in reporting violations.